Effectiveness of Audiovisual Media in Teaching Mahārah Istimāʿ Through Behaviorist and Cognitivist Approaches - Takrimah, Nila; Faruq, Ahmad Umar; Jaya, Dwi Umar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the effectiveness of audiovisual media in teaching Mahārah Istimāʿ (Arabic listening skills) by integrating behaviorist and cognitivist approaches. Responding to the challenges of passive learning methods and low student engagement, this research applies a mixed methods design to evaluate both student performance and learning experience. Twenty-nine eighth-grade students at SMPIT Adzkia, Jombang participated in the study. Quantitative data were gathered through pre- and post-tests, while qualitative insights were obtained via classroom observations and interviews. The findings indicate a notable improvement in students' listening comprehension after the use of audiovisual media. Students not only achieved higher scores but also demonstrated increased focus, motivation, and participation during lessons. Audiovisual content provided contextual and visual reinforcement, helping students associate meaning and recall information more effectively. From a behaviorist view, audiovisual media acted as a stimulus that shaped students’ responses through repetition and engagement. Cognitively, it supported active processing by combining visual and auditory input, which enhanced understanding and memory retention. The study concludes that audiovisual media is an effective instructional tool for improving Arabic listening skills, offering both academic benefits and a more engaging learning experience. It suggests that integrating audiovisual media in language instruction can bridge pedagogical gaps, particularly in digital-era classrooms where students respond better to interactive and multisensory content.